Adoptēto mantošanas tiesība - Muceniece, Dace (Latvijas Universitāte, 2009)
Lai pilnībā izprastu bakalaura darba tēmu- adoptēto mantošanas tiesība, ir jāizpēta tā veidošanās, tās iemesli un attīstība. Līdz ar to autore darba ietvaros izpētīja adoptēto mantošanas tiesības tiesisko regulējumu sākot no Babilonijas laikiem līdz pat atjaunotā Civillikuma 1992. gadā spēkā esošajai redakcijai. Darba galvenais mērėis ir izpētīt adoptēto mantošanas tiesības tiesisko regulējumu Latvijas Republikas Civillikumā, kas tiek piemērots visā Latvijas Republikas teritorijā. Tāpat autores mērėis ir noskaidrot vai Civillikumā pastāv kādas pretrunas un neskaidrības, kas saistītas ar adoptēto mantošanas tiesību un izvirzīt priekšlikumus, kuru īstenošana nodrošinātu likuma nepilnību novēršanu. Lai gūtu pilnīgāku ieskatu par adoptēto mantošanas tiesības problēmjautājumiem, autore bakalaura darba ietvaros ir salīdzinājusi Civillikumu ar ārvalstu normatīvajiem aktiem, kas regulē adoptēto mantošanas tiesības. Autore padziĜināti uzmanību ir veltījusi atšėirīgajam ārvalstu normatīvo aktu regulējumos salīdzinot ar Civillikuma regulējumu, un šo salīdzinājumu rezultātā autore guva dažus ieteikumus, kurus varētu piemērot pastāvošajā regulējumā. Darba tapšanas gaitā, izanalizējot Civillikuma regulējuma adoptēto mantošanas tiesības problēmjautājumus, autore ir izdarījusi secinājumus par pastāvošo stāvokli un izvirzītos iespējamos problēmu risinājumus apkopojusi kopsavilkumā. Bakalaura darba tapšanas rezultātā autore ir secinājusi, ka Civillikuma tiesību normas par adoptēto mantošanas tiesību nenodrošina šo tiesību institūta pareizu un taisnīgu piemērošanu. Autore problēmjautājumu risināšanai piedāvā veikt konkrētus grozījumus Civillikumā, kura rezultātā Civillikuma normas tiks saskaĦotas un līdz ar to tiks garantēta pareiza un taisnīga šo normu piemērošana.

In order to understand the theme of the Bachelor’s Paper – Right of Inheritance for Adoptee, its establishment, reasons and development shall be researched. The Author hereby within the framework of the Paper has researched legal regulation of hereditary right of adopted ones, starting from the period of Babylonia times till the renewed Civil Law valid redaction of 1992. The main purpose of the Paper is to research the legal regulation of hereditary rights of adopted individuals in the Civil Law of the Republic of Latvia which is being applied in the whole territory of the Republic of Latvia. Similarly the Author’s purpose is to find out whether in the Civil Law are some contradictions or uncertainties concerning hereditary right of adopted ones and to propose suggestions whose implementation would ensure elimination of law deficiencies. In order to gain some broader insight into problem issues of hereditary right of adopted ones, the Author within the framework of the Bachelor’s Paper has compared the Civil Law with laws and regulations of foreign countries which regulate the hereditary right of the adopted. The Author has given deepened attention to the differences between rules of foreign laws and regulations and regulation of the Civil Law; wherewith in the result of such comparison, the Author has gained some suggestions which could be applicable to the current regulation. In the procedure of the Paper development, by analysing problem issues of hereditary right of adopted ones according to the regulation of the Civil Law, the Author has made some conclusions concerning the current situation, and the proposed solutions for these problems were included in the summary by the Author. In the result of the Bachelor’s Paper development, the Author has concluded that legal norms of the Civil Law concerning the hereditary right of adopted ones do not ensure a correct and just application of this institute of rights. For the salvation of these problem issues, the Author suggests managing certain amendments in the Civil Law in order to coordinate the norms of the Civil Law and, consequently, a correct and just application of these norms will be guaranteed.
Right of Inheritance for Adoptee
Keywords: Juridiskā zinātne